Anthropogenic influences on morphological changes in the Progo River, Daerah Istimewa Yogyakarta Province, Indonesia - Akhmad Zamroni; Bayurohman Pangacella Putra; Haris Nur Eka Prasetya (Center for Science and Technology, IAIN Surakarta, 2020)
Changes in the river morphology require knowledge of the suite of drivers that control it, whether natural or human. The study aims to analyze the anthropogenic influences on morphological changes in the Progo River using Google Earth Images. It is essential to know the recent changes in the morphology of the Progo River so that stakeholders can make policies to control human activities that influence the morphology changes of the Progo River. The study area is located in Bantul Regency, Daerah Istimewa Yogyakarta Province, Java Island, Indonesia. The size of ​​the Progo River watershed is around 17,432 square kilometers. Google Earth Images analysis is carried out to analyze the morphological changes of the Progo River from 2012 to 2019. The result shows that land-use changes due to dam construction affected the sediment supply downstream of the dam. In addition, land-use changes around the Progo River due to the opening of agricultural land and settlement areas had an effect on decreasing the infiltration area, so that the number of trees holding the soil from erosion was reduced, producing more eroded sediment that flowed to the river. Sand mining in the river could cause the deepening of water depths and a decrease in the average height of the riverbed.